A rare case of isolated cervical intramedullary neurosarcoidosis, successfully treated using a combination of prednisolone and mycophenolate mofetil (Indian Journal of Case Reports, 2021)
Isolated spinal cord intramedullary neurosarcoidosis (NS) in the absence of systemic involvement is exceptionally rare, and the diagnosis can be challenging. A 41-year-old female presenting with bilateral limb weakness was referred to us with a clinical and radiological diagnosis of an intramedullary spinal cord tumor. A biopsy done from the mass was suggestive of an inflammatory lesion with no evidence of neoplasia. Following the report, she was treated with steroids that resulted in an initial symptomatic relief followed by worsening without regression of the mass. Hence, a laminotomy and decompression of the mass were done. The intraoperative smear examination showed a granulomatous lesion that was characterized on histopathology as a non-necrotizing chronic granulomatous meningomyelitis. A final diagnosis of isolated intramedullary NS was considered based on clinical features of waxing and waning response to steroids, intramedullary and leptomeningeal enhancement on radio imaging, histopathological findings of non-necrotizing granulomatous lesion, and exclusion of systemic disease. She was treated with steroids along with mycophenolate mofetil. On follow-up, there was a significant improvement in clinical symptoms.